The process of acceptance by parents of children with special needs who are victims of sexual violence at an early age - Wahyunnisa Aisy Agustini; Sri Ernawati; Anniez Rachmawati Musslifah (Jurnal Konseling dan Pendidikan, 2025)
Cases of sexual violence against children with special needs (CWSN) in Indonesia continue to rise, placing parents under layered psychological pressures that remain poorly understood. This study aims to analyze how parents construct self-acceptance through emotional dynamics, the reconstruction of caregiving roles, and the use of social–spiritual support after their children experience sexual violence in early childhood. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews with four parents in West Java whose children were identified as victims, and were analyzed using thematic analysis to identify recurring experiential patterns. The findings reveal three main themes: (1) initial emotional turmoil characterized by shock, anger, fear, and intense guilt; (2) reconstruction of caregiving meaning, including role adjustments and heightened protective responses as part of restoring parental identity; and (3) psychological strengthening through social and spiritual support, which forms the foundation for developing self-acceptance. The results indicate that self-acceptance in this context is multidimensional and shaped by relational factors as well as cultural values. This study offers novelty by highlighting the unique characteristics of self-acceptance among parents of CWSN who are victims of sexual violence. Its implications provide an essential basis for developing psychosocial interventions that are more sensitive to the trauma experienced by CWSN families.